(untitled) (Journal of Social Sciences Review, 2024)
The current Russia-Ukraine war is defining the world in politics, economics and security, especially for the United States. This study delves into the contribution and reaction of the US to the ongoing dispute from the view of Social Contract and Interest Group theories, which serve to pace the understanding of US led political, economic and military support to Ukraine. It also focuses on the interplay between state obligations, interest group influence and strategic calculations that motivate the policy decision making by the United States. Through such a convoluted journey into some of the prominent contending forces, such as the US government, interest groups, and Ukraine, this article goes on to say how, at the present extreme strain of geopolitics, all these machinery work on US decisions in holding its role as a world power. The analysis shows that the United States is involved in multilayered commands throughout moral, economic and strategic types and thus far-reaching impact on foreign relations.